Synthesis of nanocrystalline alumina (Al2O3) particles from an aqueous precursor by flame-assisted spray pyrolysis. (2018) - Jolly, Bobu Manuel; Bhattacharya, S.S.
Abstract: Nanocrystalline alumina particles were successfully synthesized in an indigenously built flame-assisted spray pyrolysis (FASP) setup. Aluminium nitrate nonahydrate was dissolved in deionized water in the desired amount to get a precursor solute concentration of 0.01 mol L -1 . The solution was then atomized by using a jet nebulizer. The droplets were then pyrolyzed in an oxy-LPG (liquifiedpetroleum gas) flame producing nanocrystalline alumina particles which were confirmed by x-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis. Particle morphology was studied using scanning electron microscopy (SEM). The synthesized powders were predominantly metastable transition aluminas exhibiting spherical morphology and were unagglomerated. The synthesized powders were then calcined at 1473 K for 2 hour to transform into the stable α-Al2 O3 (corundum) phase.